PERSETUJUAN TERTULIS MENTERI DALAM NEGERI TERHADAP PENETAPAN PERATURAN DAERAH DAN PERATURAN KEPALA DAERAH OLEH PENJABAT BUPATI - Ajeng Aulia Rahmasari; Aminuddin Kasim; Imran Imran (Universitas Tadulako, 2025)
This study aims to comprehensively examine the legal basis, procedures, and implications of the written approval mechanism given by the Minister of Home Affairs for the stipulation of Regional Regulations and Regional Head Regulations by Acting Regents. In the context of regional autonomy, this study emphasizes the importance of regional regulations as a tool to achieve equitable public welfare and accelerate the democratization process in the regions. Regional autonomy gives authority to local governments to regulate and manage government affairs and the interests of local communities in accordance with the provisions stipulated in the 1945 Constitution of the Republic of Indonesia and Law Number 23 of 2014 concerning Regional Government. This research also emphasizes the urgency of filling vacant regional head positions, which are part of the government structure needed to achieve state goals collectively and continuously. Thus, the acting regent has an important role in carrying out the duties and authorities necessary to achieve these goals. The results of the research are expected to provide input for the improvement of laws and regulations related to the formation of regional legal products, as well as provide recommendations to the central government and local governments to improve the written approval mechanism to make it more effective and efficient. This research is expected to contribute to increasing the effectiveness of regional autonomy and legal certainty in governance in Indonesia.